Who will win the ozone game? On building and sustaining cooperation in the Montreal protocoll on substances that deplete the ozone layer - Johannes Heister (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
This paper presents an analysis of the Montreal Protocol on Substances that Deplete the Ozone Layer. It advances the view that the Developing World did not exploit its relatively strong bargaining position in negotiations over sidepayments and that the concessional ten-year grace period for Jess developed countries is a cause of instability of the agreement. The paper derives conditions under which sidepayments and sanctions can produce stable cooperation. It applies basic non-cooperative game theory and the subgame perfect Nash equilibrium as solution concept and compares the non-cooperative outcome with the Nash bargaining solution of a hypothetical cooperative game.
Keywords: 330; Ozonschicht; Klimaschutz; Internationale Umweltpolitik; Spieltheorie; Verhandlungstheorie; Theorie; Welt